Overnight Immune Regulation and Subjective Measures of Sleep: A Three Night Observational Study in Adolescent Track and Field Athletes - Thomas Steidten; Thomas Steidten; Philipp Baumbach; Rico May; Brunhild Gabriel; Marco Herbsleb; Adrian Markov; Urs Granacher; Michael Kellmann; Michael Kellmann; Wilhelm Bloch; Holger H. W. Gabriel; et al. (Frontiers Media S.A., 2021)
To ensure health maintenance of young athletes, immunological stress due to physical exercise has to be balanced for performance development and health maintenance. Sleep is an important influencing factor for immune regulation because of its regenerating effect. In an attempt to assess overnight immune regulation, this observational study aimed to examine associations between changes in capillary immunological blood markers and measures of sleep in adolescent athletes. Over a period of three nights, 12 male (n = 6) and female (n = 6) adolescent track and field athletes aged 16.4 ± 1.1 years were monitored for their sleep behavior (e.g., sleep duration, sleep depth) and immune regulation by using subjective (e.g., sleep) and objective (capillary blood markers) measurement tools. Over the 4 day (three nights), athletes followed their daily routines (school, homework, free time activities, and training). Training was performed for different disciplines (sprint, hurdles, and long-jump) following their daily training routines. Training included dynamic core stability training, coordination training, speed training, resistance training, and endurance training. Capillary blood samples were taken 30-45 min after the last training session (10:00-12:00 a.m. or 5:00-6:00 p.m.) and every morning between 7:00 and 10:00 a.m. Changes in capillary blood markers from post-training to the next morning and morning-to-morning fluctuations in capillary blood markers were analyzed over a three-night period using a generalized estimating equations (GEE) statistical approach. Associations of overnight changes with measures of sleep were analyzed using GEE. We found significant decreases in white blood cell count (WBC), granulocytes (GRAN), granulocytes% (GRAN%), monocytes (MID), and granulocyte-lymphocyte-ratio. In contrast, lymphocytes% (LYM%) increased significantly and systemic inflammation index showed no difference from post-training to the next morning. Furthermore, there was a significant decrease in WBC and GRAN between morning 1 and morning 3. At morning 4, values returned to baseline (morning 1), irrespective if athletes performed a training session or rested on day 3. Furthermore, sleep duration was significantly and negatively associated with changes in WBC (βz = −0.491) and lymphocytes (βz = −0.451). Our results indicate that overnight sleep duration is an important parameter of immunological overnight regulation for adolescent athletes.